The making of an imperial polity : civility and America in the Jacobean metropolis - Working, Lauren, 1985- (Cambridge : Cambridge University Press, 2020)
Bringing to life the interaction between America, its peoples, and metropolitan gentlemen in early seventeenth-century England, this book argues that colonization did not just operate on the peripheries of the political realm, and confronts the entangled histories of colonialism and domestic status and governance. The Jacobean era is reframed as a definitive moment in which the civil self-presentation of the elite increasingly became implicated in the imperial. The tastes and social lives of statesmen contributed to this shift in the English political gaze. At the same time, bringing English political civility in dialogue with Native American beliefs and practices speaks to inherent tensions in the state's civilizing project and the pursuit of refinement through empire. This significant reassessment of Jacobean political culture reveals how colonizing America transformed English civility and demonstrates how metropolitan politics and social relations were uniquely shaped by territorial expansion beyond the British Isles. This title is also available as Open Access.
Cultivation and the American project -- Colony as microcosm : Virginia and the metropolis -- Cannibalism and the politics of bloodshed -- Tobacco, consumption, and imperial intent -- Wit, sociability, and empire.
Title from publisher's bibliographic system (viewed on 15 Jan 2020).
Keywords: Indians -- History -- 17th century; Indians -- Foreign public opinion, British -- History -- 17th century; Public opinion -- Great Britain -- History -- 17th century; Imperialism -- Public opinion -- History -- 17th century; Etiquette -- England -- History -- 17th century; Great Britain -- Politics and government -- 1603-1625.; Great Britain -- Colonies -- America -- Public opinion -- History -- 17th century; Great Britain -- Colonies -- America -- History -- 17th century; Great Britain -- Civilization -- American influences; Great Britain -- Civilization -- 17th century; England -- Social life and customs -- 17th century